The Effect of Using Cake Application on Students Speaking Skill of the 8th Grade at SMP Negeri 3 Tembuku - Ida Bagus Putu Guna Agastia; Ni Putu Ratni; I Dewa Gede Rat Dwiyana Putra (Indo Publishing, 2026)
This study aimed to determine whether there was a significant effect of Cake application on students speaking skill at the eighth grade of SMPN 3 Tembuku. This study used a quasi-experimental method with a non-equivalent control group design. The population of this study was the eight-grade students of SMP N 3 Tembuku. The sample consisted of 54 students, divided into 27 students in the experimental class and 27 students in the control class. The instruments used in this study were pre-test and post-test in the form of speaking tests. The data were analyzed by using ANCOVA. The result showed that the pre-test score had a significant effect on the post-test score, F(1,51) = 129.992, p = 0.001. After controlling the pre-test scores as a covariate, there was a significant difference between the experimental class and the control class, F(1,51) = 32.491, p = 0.001, ηp² = 0.389. This indicated that the students who were taught by using Cake application achieved better speaking skill than those who were taught by using Busuu application. Therefore, the use of the Cake application had a significant effect on students’ speaking skill.